Pengembangan Taman Kota Sebagai Ruang Ketiga (Third Place) Di Kota Banda Aceh - Syifaurrahmah Syifaurrahmah; Sylvia Agustina; Myna Agustina Yusuf (Jurnal Realitas Sosial, 2025)
Rapid urban growth and population increases in Banda Aceh have heightened the need for public spaces that support community interaction. City parks have emerged as potential "third places," providing environments distinct from home and work. This study evaluates three parks in Banda Aceh — Blang Padang Field Park, Sari/Bustanussalatin Park, and Krueng Neng Park — against criteria such as openness, flexibility, and contextuality relevance. Using mixed methods, including field surveys, observations, and questionnaires distributed to 100 visitors, the research highlights these parks as inclusive social hubs. Each park has distinct roles: Blang Padang serves as a social and sports hub, Taman Sari emphasizes historical and cultural connections, and Krueng Neng prioritizes family-oriented facilities like playgrounds and fishing areas. Despite their benefits, issues like cleanliness, safety, and inadequate facilities need attention to enhance their utility. Recommendations include adding sports facilities and Wi-Fi to Blang Padang for students and freelancers, transforming Taman Sari into a cultural hub with art and discussion spaces, and enhancing Krueng Neng with better family recreation amenities and accessibility. With improved management, these parks could foster social bonds, offer dynamic interaction spaces, and elevate Banda Aceh residents’ quality of life.